Preparation and characterization of bifunctional oxidative and acidic catalysts Nb2O5/TS-1 for synthesis of diols - Prasetyoko, Didik (Elsevier, 2005)

(untitled)
Bifunctional oxidative and acidic catalyst was prepared by incorporation of titanium ion (Ti4+) and niobic acid in zeolite molecular-sieve. The catalysts being active both in oxidation reactions due to the presence of tetrahedral Ti4+, and acid-catalyzed reactions due to the presence of niobic acid. Nb/TS-1 was prepared by hydrothermal synthesis of TS-1, calcination in air and subsequent impregnation of niobium into TS-1. The sample was characterized by XRD, FTIR, UV-vis DR, TPR and pyridine adsorption techniques. The XRD analysis of Nb/TS-1 revealed that the MFI structure of the TS-1 support was found to be intact upon incorporation of niobium. The infrared spectra showed that the tetrahedral titanium in the TS-1 is still remained after impregnation with niobium while based on the UV-vis DR result, the niobium species are in the octahedral structure. On the basis TPR and infrared of hydroxyl groups results, it is concluded that niobium species interacted with the silanols on the surface of TS-1. Pyridine adsorption study shows both Brønsted and Lewis acid sites are present in Nb/TS-1. The catalytic results in the transformation of 1-octene to 1,2-octanediol through the formation of 1,2-epoxyoctane by using Nb/TS-1 indicate that the production of epoxide and diol was correlated with the presence of oxidative and Brønsted acidic sites in the catalyst.